Desenvolvimento de dispositivo para calibração de sensor de umidade do solo e aplicação em sensores tipo tensiômetro eletrônico e resistência elétrica - Leão, Raimundo Alípio de Oliveira (2004)
Na apparatus for soil moisture calibration was developed and built (DCSUS). The moisture was controlled indirectly by controlling the soil water matrix potenctial using both a porous plate funnel and a pressure chamber system. A 3.0 m high tower wal built in steel and a scale installed on its top. The scale components were an I-bean articulated in its center by a set of bearings and bushings and a shaft. The bian was welded in its middle point to the shaft and a horizontal soil column with undisturbed soil contained by an acrylic cylinder installed on one of its ends, and a 50 N capacy load cell on the other end. The following sensors were installed: a granular matrix sensor (Watermark), an electronic tensiometer sensor, air temperature sensors and soil temperature sensors. Moisture sensor readings, as well as from the load cell and temperature sensor were taken in real time at a 3 Hz frequency from 01/15 to 05/27/2004. The data acquisition system was made of a 12-bit analog/digital coverter, an AMD188 microcontroller and an RS232 interface. Data was stored daily and applied to obtain the parameters of calibrations, sensitivity and the effect of temperature on the system. The apparatus resulted in sensitivity to moisture change of 13,33 mL of water. The load cell displayed some sensitivity to daily temperature variation, with an error of 0,25%. The Watermark sensors were not affected by air temperature variation, but displayed sensitivity to variation on the supplied voltage. The electronic tensiometers, however, were more sensitive to temperature with errors of 3.5% for higher matric potentials (-3.82 to -3.92 kPa) and 5.5% for lower matric potentials (-44.5 to -51 kPa). The DCSUS showed to be efficient in monitoring variations soil moisture, displaying a minimum reading 4.244E-4 cm3.cm-3.